A distribution-free newsvendor model with balking penalty and random yield - Chongfeng Lan; Huanyong Ji; Jing Li (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this paper is to extend the analysis of the distribution-free newsvendor problem under the circumstance of customer balking, which usually occurs when customers are reluctant to buy products if the available inventory falls below a threshold level. Design/methodology/approach: A new tradeoff tool is provided as a replacement of the traditional one to weigh the holding cost and the goodwill costs segment: apart from the shortage penalty, the balking penalty is introduced. Furthermore, such research methodology is employed in the case of random yield. Findings: A model is presented for determining both an optimal order quantity and a lower bound of the profit under the worst possible distribution of the demand. We also study the effects of shortage penalty and the balking penalty on the bias of the optimal order quantity, which have been largely bypassed in the existing distribution-free single period models with balking. Numerical examples are presented to illustrate the result. Originality/value: The incorporation of balking penalty and random yield represents an important improvement in inventory policy performance for distribution-free newsvendor problem when customer balking occurs and the distributional form of demand is uncertain.
Keywords: 650; newsvendor model; distribution-free; balking penalty; random yield